Pengaruh Social Media Marketing dan Brand Awareness Terhadap Keputusan Pembelian Produk Hand & Body Lotion Marina - Cahyati, Putri Farah; Yunita, Nindya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The research analysis aims to determine the effect of Social Media Marketing and Brand Awareness on purchasing decisions for Hand & Body Lotion Marina products (Case Study in the Medan Sunggal District Community). This study uses multiple linear regression analysis. The sample in this study was 100 respondents. Primary data collection using a questionnaire. The results of the study showed that the test results for the social media marketing variable showed a t-count value of 4,716 > t-table of 1.98 with a significant value of 0.000 <0.05, then the hypothesis H1 is accepted and H0 is rejected, meaning that social media marketing has a positive and significant effect partially on purchasing decisions for Hand & Body Lotion Marina. The test results for the brand awareness variable showed a t-count value of 3.229 > t-table of 1.98 with a significant value of 0.002 <0.05, then the hypothesis H2 is accepted and H0 is rejected, meaning that brand awareness has a positive and significant effect partially on purchasing decisions for Hand & Body Lotion Marina. The results of simultaneous testing show that the value of F count is 276,610 which is greater than 3.07 and the significant value of 0.000 is less than 0.05 so it can be concluded that hypothesis 3 is accepted and hypothesis 0 is rejected so it can be concluded that social media marketing and brand awareness have a positive and significant effect simultaneously on purchasing decisions for Hand & Body Lotion Marina.